Direct product and wreath product of transformation semigroups - Majumdar, Subrata; Dey, Kalyan Kumar; Hossain, Mohd Altab (GANIT: Journal of Bangladesh Mathematical Society, 2012)
In this paper direct product and wreath product of transformation semigroups have been defined, and associativity of both the products and distributivity of wreath product over direct product have been established. DOI: http://dx.doi.org/10.3329/ganit.v31i0.10303 GANIT J. Bangladesh Math. Soc. (ISSN 1606-3694) 31 (2011) 1-7